Black aortic valve: Minocycline pigmentation complicating treatment of pyoderma gangrenosum. Issue 12 (2nd September 2019) - Nagata, Tomoki; Hasegawa, Takao; Johno, Hiroyuki
Abstract: We describe the case of a 75‐year‐old male with pyoderma gangrenosum (PG) who had severe aortic insufficiency and moderate mitral regurgitation. He had been taking minocycline for 15 years to treat PG. He underwent aortic valve replacement and mitral valve repair. Aortotomy revealed a black discoloration of the aortic valve and sinus of Valsalve.